DESIGNING STYLE OF WITHERING TEA TROUGH FOR TEA MANUFACTURING INDUSTRY OF VIETNAM - Chương, Đỗ Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYSuccess in researching on designing withering tea trough helps small and medium companies to apply easily to their producing condition. Depend on specific scale and producing condition, producer can choose for them the suitable side and composition of the withering tea trough. When using these kinds of withering tea trough, the product quality is considerably improved; this may create good condition to curling and fermenting afterwards. From that point, using these kinds of withering tea trough can make the black tea quality advanced and stable. Besides, withering tea trough also helps producers to save energy, reduce environment pollution which is the big problem of our society and all countries in the world.